2019
DOI: 10.1101/776237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust effects of corticothalamic feedback and behavioral state on movie responses in mouse dLGN

Abstract: 8Neurons in the dorsolateral geniculate nucleus (dLGN) of the thalamus are contacted by a large number of feedback synapses from cortex, whose role in visual processing is poorly understood. Past studies investigating this role have mostly used simple visual stimuli and anesthetized animals, but corticothalamic (CT) feedback might be particularly relevant during processing of complex visual stimuli, and its effects might depend on behavioral state. Here, we find that CT feedback robustly modulates responses to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 184 publications
(465 reference statements)
2
18
0
Order By: Relevance
“…Sustained optogenetic activation of L6CTs in V1 with different levels of continuous light strongly suppresses visually evoked and spontaneous activity in the dLGN and pulvinar, yet controlled 10-Hz stimulation of this same population leads to facilitating spiking in both areas. These activity changes are accompanied by changes in burst versus tonic modes of firing, which is consistent with previous reports that corticothalamic feedback can modulate thalamic firing mode (7,8,11,12,32). Remarkably, we also observed similar facilitating spiking at 10 Hz in the visTRN, yielding virtually indistinguishable effects between the visTRN and pulvinar/dLGN with L6CT train photostimulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sustained optogenetic activation of L6CTs in V1 with different levels of continuous light strongly suppresses visually evoked and spontaneous activity in the dLGN and pulvinar, yet controlled 10-Hz stimulation of this same population leads to facilitating spiking in both areas. These activity changes are accompanied by changes in burst versus tonic modes of firing, which is consistent with previous reports that corticothalamic feedback can modulate thalamic firing mode (7,8,11,12,32). Remarkably, we also observed similar facilitating spiking at 10 Hz in the visTRN, yielding virtually indistinguishable effects between the visTRN and pulvinar/dLGN with L6CT train photostimulation.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of first-order nuclei, like the dorsolateral geniculate nucleus (dLGN) in the visual system, this corticothalamic feedback originates from layer 6 (L6). L6 corticothalamic neurons (L6CTs) have been classically described as providing "modulatory" feedback to the dLGN (1,2) that may influence response gain (3)(4)(5)(6)(7)(8), temporal precision (9,10), spatiotemporal filtering (6,10,11), sensory adaptation (12), and burst versus tonic firing modes (7,8,11,12). Still, how these L6CTs might perform these various functions is not well understood.…”
mentioning
confidence: 99%
“…We think it is unlikely that intracortical rebound effects drive our main conclusions, because, firstly, such effects have not been prominent in previous studies quantifying the lateral extent of cortical suppression 53, 131 , and secondly, we have found a consistent spatial pattern of CT feedback effects in dLGN with both global V1 suppression and L6CT photoactivation, which likely recruit intracortical circuits in different ways. To rule out the effects of polysynaptic circuits during global suppression, it is not sufficient to selectively suppress L6CT pyramidal cells at the level of V1 34, 132 , because they have an intracortical axon collateral that targets layer 5 50 , and also make privileged connections with a translaminar PV+ interneuron subtype in L6 51, 52 , which in turn strongly regulates the gain of the entire V1 column 34, 51, 52 . Instead, a more promising next step would be to directly suppress axon terminals of L6CT pyramidal cells at the thalamic target.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies in animals have also shown that cortical feedback projections robustly modulate responses of early visual areas when sensory evidence is low, or the stimulus is difficult to segregate from the background figure (Hupe et al, 1998). A recent study has also found cortical feedback modulated the activity of neurons in the dorsolateral geniculate nucleus (dLGN), which was less consistent when presenting simple vs. complex grating stimuli (Spacek et al, 2019). Therefore, varying perceptual difficulty seems to engage different networks and processing mechanisms, and we show here that this also pertains to faces: less difficult stimuli such as our high-coherence faces seem to be predominantly processed by the feed-forward mechanisms, while more difficult stimuli such as our low-coherence faces recruit both feed-forward and feedback mechanisms.…”
Section: Discussionmentioning
confidence: 99%